Endocrine Disruptors - Ediz Yeşilkaya (Güncel Pediatri, 2008)
Endocrine disruptors are of special interest because they mimic, block, or in some way alter the activity of endogenous chemicals that are synthesized by the endocrine system. Besides many other organs, they especially affect the urinary system and the thyroid glands. Endocrine-disrupting chemicals are typically identified as compounds that can interact with oestrogen or androgen receptors and thus act as agonists or antagonists of endogenous hormones. During the last decade, numerous studies have been published, reporting an increase in reproductive organ anomalies, as well as in testicular cancer, and a decline in the relative number of male births, and in semen quality. In this review, the effects of endocrine distruptors on the reproductive health are discussed in the light of the recent literature. (Journal of Current Pediatrics 2008; 6: 76-82)